The Importance of the Exceptional in Tackling Riddles of Consciousness and Unusual Episodes of Lucidity - Nahm, Michael (Journal of Anomalous Experience and Cognition, 2022)
The problem of how biochemical processes in the brain give rise to conscious experience is still unanswered. This paper aims at stimulating the debate surrounding this enigma by advocating the study of unusual and anomalous aspects of consciousness. For this purpose, the contents of this paper are organized in three parts. In the first part, I provide a brief overview on unsolved riddles of the mind. These include unusual episodes of lucidity that have been termed terminal lucidity and paradoxical lucidity. Because the use of these terms has sometimes been inappropriate in recent literature, I clarify the basic meanings of these two concepts in the second part. The third part contains suggestions for future research. Specifically, I argue that the field of studies into episodes of lucidity in dementias and the field of studies into end-of-life experiences, such as near-death visions, should engage in an active dialogue in order to build bridges between these disciplines. Such a dialogue will enable a better understanding of the whole spectrum, and thus, possible circumstances, causes and underpinnings of lucid episodes. In sum, this paper argues that the study of lucid episodes such as terminal lucidity, paradoxical lucidity, and related occurrences holds enormous significance for improving our understanding of brain functions and accompanying states of consciousness – from a practice-orientated perspective in the contexts of the dementias and dealing with end-of-life experiences, and from a theoretical perspective in the context of the scientific debate about the nature of consciousness.